2010
DOI: 10.1007/s12291-010-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Level of T3, T4, TSH and the Association of A/G Polymorphism with CTLA-4 Gene in Graves’ Hyperthyroidism among South Indian Population

Abstract: Graves' disease (GD) is an organ-specific heterogenous autoimmune disorder associated with T-lymphocyte abnormality affecting the thyroid, eyes and skin. GD is a multifactorial disease that develops as a result of complex interaction between genetic susceptibility genes and environmental factors. It has been suggested that the Cytotoxic T lymphocytes associated molecule-4 (CTLA-4) is a genetic susceptibility candidate for GD. The present study was focused on A/G polymorphism at position 49 in exon-1 of the CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In accordance with our results, studies conducted among different populations showed an association of CTLA-4 gene 49 A/G polymorphism with Graves' disease including Caucasians (Yanagawa et al, 1995), Japanese (Yanagawa et al, 1997), Koreans (Park et al, 2000), Chinese children (Chong et al, 2008) and Taiwanese (Weng et al, 2005) and in South Indian population (Veeramuthumari et al, 2011). However, the study of Frydecka et al (2004), showed that the distribution of CTLA-4 exon 1 A (49)G genotype, allele and phenotypic frequencies did not differ between patients with GD and healthy subjects in Polish population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our results, studies conducted among different populations showed an association of CTLA-4 gene 49 A/G polymorphism with Graves' disease including Caucasians (Yanagawa et al, 1995), Japanese (Yanagawa et al, 1997), Koreans (Park et al, 2000), Chinese children (Chong et al, 2008) and Taiwanese (Weng et al, 2005) and in South Indian population (Veeramuthumari et al, 2011). However, the study of Frydecka et al (2004), showed that the distribution of CTLA-4 exon 1 A (49)G genotype, allele and phenotypic frequencies did not differ between patients with GD and healthy subjects in Polish population.…”
Section: Discussionsupporting
confidence: 92%
“…The lowest ''G'' allele Science Publications AJBB frequency (48%) was noted in Caucasian GD population and among healthy individuals in Iranian (37%) (Kalantari et al, 2003) and Caucasian population (38%) (Bednarczuk et al, 2003). The study of Veeramuthumari et al (2011), shows that the ''G'' allele frequency is 63% among South Indian population, which is comparable to that of the Taiwanese ''G'' allele frequency (67%) (Weng et al, 2005) and Koreans (68%) (Park et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Methodology to be followed for the discovery of single nucleotide polymorphism in polycystic kidney disease Genomic DNA preparation: [68,69].…”
Section: Trends In Potential Therapies and Clinical Trialsmentioning
confidence: 99%
“…Electrophoretic analysis of genomic DNA: the isolated DNA was confirmed by 0.7% agarose gel electrophoresis [68,69].…”
Section: Trends In Potential Therapies and Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation